HEALTH RISKS OF MUSLIM PILGRIMAGE - (:unkn) unknown (NOBEL ILAC, 2015)
Hajj, the pilgrimage to Mecca and surrounding holy sites is a religious exercise, which every physically able Muslim must undertake once in his of her lifetime. Every year 1.5 million Muslim pilgrims converge in Saudi Arabia for the world's largest annual gathering. This unique event, which might possess some public health implications on a global scale, is exhausting both physically and mentally for every pilgrim due to extreme heat and crowded accommodation. Therefore it's essential that the physicians are aware of the health risks and surroundings of the pilgrims in order to provide appropriate preparation. Apart from mandatory meningococcus vaccination, immunizations against pneumococcus and influenza should be recommended, appropriate physical training to increase their endurance beforehand must be emphasized and education about hygiene possible complications should be provided. To minimize the health risks that arise due to gathering of masses there are many standard precautions in effect however recent issues such as Middle East Respiratory Syndrome Coronavirus (MERS-CoV), Ebola hemorrhagic fever and cholera epidemics mandate new precautions. In this article we aim to address the health risks pilgrims face and how physicians can provide better counseling before this travel.
Keywords: Coronavirus infections; Islam; risk factors; disease outbreaks; travel; public health; TUBERCULOSIS; PREVENTION; INFECTION; HEPATITIS; ADMISSION